Role Playing Learning Method in The Subject of Aqidah Akhlak at Madrasa - Firman Mansir; Tumin Tumin; Halim Purnomo (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
This research describes and discusses about the importance of using role-playing method in Aqidah Akhlak at Madrasa. Professional teachers are those who are able to lead students to achieve maximum outcomes. This research aims to realize the learning of Aqidah Akhlak that is appropriate to the current context. Thus, teachers are required to use brilliant and different methods from the others. Aqidah Akhlak subject requires an effective method because Aqidah Akhlak has different characteristics from other subjects. That is why 21st century PAI (Islamic education) teachers need to be creative by utilizing a variety of learning methods. An effective method for Aqidah Akhlak subjects is role playing. The skills of a PAI teacher are expected to emerge from the role playing method in the Aqidah Akhlak learning process. The strategy and method of role playing are one of the components contained in the learning system. The components are capable of delivering effective and dynamic learning processes. Therefore, from various learning methods used by PAI teachers, role playing one is considered effective to make directed, capable, and effective learning based on learning goals.